2011
DOI: 10.1016/j.neuropharm.2011.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabenazine inhibition of monoamine uptake and methamphetamine behavioral effects: Locomotor activity, drug discrimination and self-administration

Abstract: Tetrabenazine (TBZ), a benzoquinolizine derivative, binds with high affinity to the vesicular monoamine transporter-2 (VMAT2), inhibiting uptake of cytosolic monoamines. The current study aimed to provide preclinical evidence supporting the potential use of TBZ as a treatment for methamphetamine abuse. Effects of TBZ on function of the dopamine transporter (DAT) and serotonin transporter (SERT) in striatal and hippocampal synaptosomes, respectively, and on VMAT2 function in isolated striatal synaptic vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…This is consistent with uptake experiments performed in synaptosomes (Meyer et al, 2011). However, the authors concluded that the ability of TBZ to inhibit uptake in synaptosomes is due to action at DAT.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with uptake experiments performed in synaptosomes (Meyer et al, 2011). However, the authors concluded that the ability of TBZ to inhibit uptake in synaptosomes is due to action at DAT.…”
Section: Discussionsupporting
confidence: 92%
“…Considerable attention has been given to positive rewarding effects associated with MA addiction (Beckmann et al, 2010;Horton et al, 2011;Kamens et al, 2005;Mahler et al, 2013;Meyer et al, 2011;Mizoguchi et al, 2004;Shabani et al, 2011Shabani et al, , 2012aWheeler et al, 2009), whereas aversive effects that could limit intake have been given less consideration (Harrod et al, 2010;Pringle et al, 2008;Shabani et al, 2011Shabani et al, , 2012bWheeler et al, 2009). Greater Figure 3 (a) Methamphetamine (MA) consumption differs by Taar1 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Also, acute administration of GZ-793A had no effect on locomotor activity when administered alone or in conjunction with METH. This finding was surprising given that VMAT2 inhibitors lobelineand tetrabenazine are able to inhibit amphetamine- and methamphetamine-induced hyperactivity (Miller et al 2001; Meyer et al 2011). Also, GZ-793A reduces striatal extracellular DA release (Horton et al 2011) which is assumed to underlie the psychomotor activating effects of psychostimulants (Wise and Bozarth 1987).…”
Section: Discussionmentioning
confidence: 99%